2012
DOI: 10.3390/ijms13021632
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Snail-1, E-Cadherin and Claudin-1 Expression in Colorectal Adenomas and Carcinomas

Abstract: We report the expression of Snail-1, E-cadherin and claudin-1 by indirect immunohistochemistry in colonic neoplasia. Snail-1 is a zinc finger transcription factor expressed in cells that already have undergone almost complete epithelial-mesenchymal transition (EMT) and have already evaded from the tumor. The main mechanism by which Snail induces EMT is downregulation of E-cadherin, of which expression was shown to be frequently downregulated in many different types of tumors, where it accompanies the invasiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 39 publications
3
39
1
1
Order By: Relevance
“…The EGF-induced changes observed in this study could be attributed to impaired TJ function, which facilitated access to the EGF receptor, EGFR. This receptor is mainly present in the basolateral region and can thus potentially induce neoplastic transformation, as suggested previously [14], [19], [38]. Controversially to our observations, a recent study showed that EGF decreased claudin-3 and -4 via MEK/ERK and/or PI3K/Akt signaling pathways in ovarian cancer cell lines [39].…”
Section: Discussionsupporting
confidence: 80%
“…The EGF-induced changes observed in this study could be attributed to impaired TJ function, which facilitated access to the EGF receptor, EGFR. This receptor is mainly present in the basolateral region and can thus potentially induce neoplastic transformation, as suggested previously [14], [19], [38]. Controversially to our observations, a recent study showed that EGF decreased claudin-3 and -4 via MEK/ERK and/or PI3K/Akt signaling pathways in ovarian cancer cell lines [39].…”
Section: Discussionsupporting
confidence: 80%
“…It is well known that tight junction expression is regulated by many factors4142, but whether lncRNAs are directly involved in this regulation has remained unclear. However, in our correlation results, lnc-TAF9-1 and occludin mRNA were shown to potentially be associated with tight junction regulation (Supplemental Table 6), and our previous data indicate that meningitic E. coli induction of VEGFA and Snail-1 downregulated the expression of tight junctions28.…”
Section: Discussionmentioning
confidence: 99%
“…Snail could directly modulate claudin-1 expression 31 and its dystopic subcellular localizations with claudin-1 helped to form cellular morphology. 32 Hence, a new regulation pathway composed of cAbl/ERK/claudin-1/snail as the downstream of TMPRSS4 in EMT regulation of colon cancer cell deserves in-depth investigation. Additionally, EMT program has been suggested to generate cells with features of CSCs 33,34 and we found that by inhibiting TMPRSS4, possibly suppressing EMT, the self-renewal ability of HCT116 could be reduced as reflected by clonogenic formation assays and CSC markers.…”
Section: Discussionmentioning
confidence: 99%